Combination of CFG and N-gram Modeling in Semantic Grammar Learning - Wang, Ye-Yi; Acero, Alex (Eurospeech 2003, 2003)
SGStudio is a grammar authoring tool that eases semantic grammar development. It is capable of integrating different information sources and learning from annotated examples to induct CFG rules. In this paper, we investigate a modification to its underlying model by replacing CFG rules with n-gram statistical models. The new model is a composite of HMM and CFG. The advantages of the new model include its built-in robust feature and its scalability to an n-gram classifier when the understanding does not involve slot filling. We devised a decoder for the model. Preliminary results show that the new model achieved 32% error reduction in high resolution understanding.